The existence of a bifurcation value of a parameter of a system of differential equations with deviating argument - Nasykhova, L. V.; Terekhin, M. T. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We prove a theorem on the existence of a nonzero periodic solution of a system of differential equations with deviation that depends both on an unknown function and on its derivative. This result is obtained for the case where the matrix of linear approximation has zero and imaginary eigenvalues if the parameter takes a critical value.